Association of Intracranial Aneurysms With Aortic Aneurysms in 125 Patients With Fusiform and 4253 Patients With Saccular Intracranial Aneurysms and Their Family Members and Population Controls. Issue 18 (17th September 2019) - Kurtelius, Arttu; Väntti, Nelli; Rezai Jahromi, Behnam; Tähtinen, Olli; Manninen, Hannu; Koskenvuo, Juha; Tulamo, Riikka; Kotikoski, Satu; Nurmonen, Heidi; Kämäräinen, Olli‐Pekka; Huttunen, Terhi; Huttunen, Jukka; et al.
Abstract : Background: Varying degrees of co‐occurrence of intracranial aneurysms (IA) and aortic aneurysms (AA) have been reported. We sought to compare the risk for AA in fusiform intracranial aneurysms (fIA) and saccular intracranial aneurysms (sIA) disease and evaluate possible genetic connection between the fIA disease and AAs. Additionally, the characteristics and aneurysms of the fIA and sIA patients were compared. Methods and Results: The Kuopio Intracranial Aneurysm Database includes all 4253 sIA and 125 fIA patients from its Eastern Finnish catchment population, and 13 009 matched population controls and 18 455 first‐degree relatives to the IA patients were identified, and the Finnish national registers were used to identify the individuals with AA. A total of 33 fIA patients were studied using an exomic gene panel of 37 genes associated with AAs. Seventeen (14.4%) fIA patients and 48 (1.2%) sIA patients had a diagnosis of AA. Both fIA and sIA patients had AAs significantly more often than their controls (1.2% and 0.5%) or relatives (0.9% and 0.3%). In a competing risks Cox regression model, the presence of fIA was the strongest risk factor for AA (subdistribution hazard ratio 7.6, 95% CI 3.9–14.9, P <0.0005). One likely pathogenic variant in COL5A2 and 3 variants of unknown significance were identified in MYH11, COL11A1, and FBN1 in 4 fIA patients. Conclusions: The prevalence of AAs is increased slightly in sIA patients and significantly in fIA patients. fIA patients are older and have more comorbid diseases than sIA patients but this alone does not explain their clinically significant AA risk.